Awareness, Self-Efficacy, and Accessibility of Community-Based Healthcare Services Among Older Adults in Timor-Leste - Domingos Ximenes; Jacqueline G. Palancos; Cicilia Nadya Buli; Beryl Ben Mergal; Giovani P. Mercado; Francisco T. Salgueiro (Mandalika Journal of Medical and Health Studies, 2025)
This study aimed to determine predictors of accessibility to community health services among older adults and to examine the relationship between knowledge, self-efficacy, and use of these services. A quantitative, descriptive-correlational, and cross-sectional research design was used. Participants were selected by probabilistic random sampling in identified communities to ensure representativeness. Data were collected using a structured questionnaire that assessed knowledge about available services, confidence in access to care, and perception of accessibility. Descriptive statistics were used to determine the levels of the main variables, while correlational, comparative, and regression analyses were applied to examine relationships, demographic differences, and predictive factors. The results indicated that knowledge and self-efficacy were significantly associated with accessibility to community health services. Higher levels of knowledge and greater self-efficacy correlated with a better perception of access to care. The selected demographic variables also showed significant differences in accessibility. Knowledge and self-efficacy emerged as significant predictors of accessibility to health services. The results of this study underscore the importance of strengthening health education, capacity-building strategies, and community interventions to improve equitable access to health services among older adults.